Development of mini-undulators for a table-top free-electron laser. (5th November 2018) - Petrov, G.; Davis, J.; Schumaker, W.; Vargas, M.; Chvykov, V.; Hou, B.; Maksimchuk, A.; Yanovsky, V.; Thomas, A. G. R.; Krushelnick, K.; Garraud, A.; Arnold, D. P.; et al.
Abstract: The development of laser wakefield accelerators (LWFA) over the past several years has led to an interest in very compact sources of X-ray radiation – such as "table-top" free electron lasers. However, the use of conventional undulators using permanent magnets also implies system sizes which are large. In this work, we assess the possibilities for the use of novel mini-undulators in conjunction with a LWFA so that the dimensions of the undulator become comparable with the acceleration distances for LWFA experiments (i.e., centimeters). The use of a prototype undulator using laser machining of permanent magnets for this application is described and the emission characteristics and limitations of such a system are determined. Preliminary electron propagation and X-ray emission measurements are taken with a LWFA electron beam at the University of Michigan.